Ethnopsychological Specifics of Arab and Mongolian Students' Orderliness - - Orsoo Tuya (Peoples' Friendship University of Russia (RUDN University), 2012)
The article discusses the results of an empirical study of the ethnopsychological characteristics of the manifestation and structure of the Arab and Mongolian students' orderliness, performed in line with A.I. Krupnov's system-functional approach to personality traits and individuality study.